2020
DOI: 10.1101/2020.08.20.20178525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of COVID-19 patients with diabetes mellitus in Kuwait

Abstract: Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) emerged in Wuhan, China, in 2019 and rapidly turned into a global pandemic, resulting in what is now known as Coronavirus Disease 2019 (COVID-19). COVID-19 has a highly variable clinical presentation, ranging from asymptomatic to severe respiratory symptoms and death. Diabetes seems to be one of the main comorbidities contributing to a worse COVID-19 outcome. Methods: In this single-center, retrospective study of 417 consecutive COVID-19 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
1
15
0
2
Order By: Relevance
“…Notably, the severity of this disease is highly variable in different populations across the world [1,2]. Since the outbreak, several studies have reported specific factors including age, gender, and pre-existing health conditions that could have contributed to the increased severity of the disease [3,4,5,6]. The genetic susceptibility to COVID-19 has also been explored by scrutinizing Angiotensin converting enzyme 2 (ACE2) genetic variations in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the severity of this disease is highly variable in different populations across the world [1,2]. Since the outbreak, several studies have reported specific factors including age, gender, and pre-existing health conditions that could have contributed to the increased severity of the disease [3,4,5,6]. The genetic susceptibility to COVID-19 has also been explored by scrutinizing Angiotensin converting enzyme 2 (ACE2) genetic variations in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients with severe cases develop ARDS and severe cardiac and renal complications, which can potentially lead to death [6,7]. Additionally, a poorer prognosis has been associated with older age, being male, and having pre-existing chronic conditions, such as hypertension, cardiovascular disease, and diabetes [8,9]. At the same time, pediatric cases have shown a milder clinical course [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization rate was 100%, subject to a positive PCR test regardless of disease severity. Cohort clinical characteristics were previously described by our group (Ali et al, 2020; Alshukry et al, 2020). The study was reviewed and granted an approval by the standing committee for coordination of health and medical research in the Ministry of Health in Kuwait (IRB 2020/1404).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical manifestations of COVID-19 patients vary broadly, ranging from asymptomatic infection to acute respiratory failure and death (Alshukry et al, 2020). It is well established now that age, gender and certain pre-existing health conditions are considered as risk factors for a severe form of the disease (Ali et al, 2020). However certain indications have suggested a possible implication for ethnicity and race as contributors to the wide disparity in COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%